GABAA receptor modulation by the volatile fractions of Sideritis species used as ‘Greek’ or ‘Turkish’ mountain tea. - Kessler, Artur; Villmann, Carmen; Sahin, Hilal; Pischetsrieder, Monika; et al. (Flavour and Fragrance Journal, 2012)
Sideritis spp. is a member of the Labiateae family, used in traditional folk medicine and as a calming tea preparation. Dichloromethane extracts of the aerial parts of four Sideritis species were prepared, and the volatile fractions were separated via solvent‐assisted flavour evaporation distillation. In vitro electrophysiological techniques were used to investigate the physiological effects of these aroma extracts on ionotropic γ‐aminobutyric acid receptors (GABAA) in comparison to extracts of Lavandula spp. (lavender) obtained by the same approach. The plant extracts of Sideritis spp. and Lavandula spp. increased the maximal current responses gated by the agonist GABA, both in whole cell patch clamp recordings as well as in two electrode voltage clamp assays. Thereby, the volatile fractions caused a dose‐dependent enhancement of GABAergic currents. Differences in activity between the various species were probably due to variations in odorant composition, either on a qualitative or quantitative basis. Thus, the plant material contains volatile organic compounds, which are able to modulate a GABA‐mediated response and thereby possibly contribute to a sedative effect in vivo. Copyright © 2012 John Wiley & Sons, Ltd.<br